The Implementation of Grammatical Error Analysis to Improve Students’ Writing Skill on Recount Text for Students Class X MIA At SMA Tri Dharma Kosgoro Dompu - Arnillah, Nadiya (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
This study is a classroom action research that focuses on the implementation of grammatical error analysis to improve students’ writing skill on recount text for students. The study conducted at SMA Tri Dharma Kosgoro Class X MIA that consisted of 25 students; 15 male and 10 female. Apart from implementing the grammar error analysis to enhance students’ writing skill, the researcher also identify some errors of students’ writing particularly on grammatical error and analyze some factors of these errors. The implementation of this research was in cycle I that consist of eight meetings. Study shows that the implementation of grammatical error analysis can enhance the students’ understanding in writing recount text. This has been shown by the improvement of student’s score. Moreover, the kinds of the students’ grammatical errors could be classified into seven categories namely errors in verb groups, errors in subject and verb agreement, errors in article, errors in pluralization, errors in conjunction, errors in preposition, and errors in pronoun. The identification of these type of grammatical error is paramount due to these could help students understand some components of grammar that students should master to improve their understanding in writing recount text.